Effect of calcium leaching on the fracture properties of concrete. (15th February 2023) - Zhang, Wenbing; Shi, Danda; Shen, Zhenzhong; Wang, Xiaohui; Gan, Lei; Shao, Wei; Tang, Peng; Zhang, Hongwei; Yu, Shuyang
Highlights: The evolution of the fracture properties of leached concrete was investigated. The crack extension resistance curve of leached concrete was firstly revealed. The variation of concrete fracture parameters with leaching time follows exponential functions. The residual value of fracture parameters of the fully leached concrete was estimated. A phase-field fracture model considering calcium leaching effects was developed. Abstract: In this work, acceleration leaching and three-point bending (TPB) tests were performed on single-notched TPB beam specimens to explore the evolution of the fracture properties of concrete subjected to calcium leaching. The load-crack mouth opening displacement ( P -CMOD) curves obtained for concrete at various leaching times were adopted to analytically calculate parameters that can reflect the fracture properties of concrete, such as the crack extension resistance ( K R ), fracture toughness ( K Ic ini and K Ic un ), elastic modulus ( E ), tensile strength ( f t ), and fracture energy ( G f ). Furthermore, a phase-field fracture model for concrete that considers calcium leaching effects is established by incorporating the time-dependent damage variables E, f t, and G f . The results reveal that the K R curves of the leached concrete increase with crack propagation but lower and flatten with more leaching time. The fracture parameters K Ic ini, K Ic un E, f t, and G f rapidly decrease with leaching time in the first 60 days. However, with more leaching time, the impact of calcium leaching on the concrete fracture properties gradually diminishes. The variation in fracture parameters of leached concrete can be described by a series of exponential functions. The residual value fracture parameters of the fully leached concrete are estimated to be approximately 60–80 % of those of sound concrete. The established fracture model reproduces the P -CMOD curves of concrete at each leaching time, which verifies the rationality of the model. The numerical simulation reveals that crack propagate faster in leached concrete than in sound concrete, and leached concrete is more prone to cracking.